Eoko - Ole Pere (Symphony in the Flint Hills, 2015)
This is a poem that is half sung and half spoken and is known as Eoko in Maa. It is spoken (or sung) by men, mainly warriors (ilmurran), to relate their accomplishments. They are normally highly poetic and rhythmic. Note the repetitions and the imagery. Ole Pere, the composer, is from the Purko section of the Narok district. This Eoko was recorded at his home in 1976.
Keywords: poem; Africa; African; Eoko; spoken; history; people; cattle; cows; landscape; country